Plant Cryopreservation: A Practical Guide - Reed, Barbara B.M (Springer New York : Imprint: Springer, 2008)
Plant Cryopreservation: A Practical Guide is a unique resource for plant scientists in many fields. This compilation provides over 100 ready-to-use protocols for plant types from algae and bryophytes to a range of flowering plants. It includes techniques for diverse plant parts such as dormant buds, pollen, and apical meristems, and for cell types such as suspension and callus cultures. Five introductory chapters describe theoretical principles, practical aspects of long-term cryopreserved storage, and details of the main cryopreservation techniques. The remaining 14 chapters are separated by plant type. Each chapter briefly reviews the literature and includes ready-to-use protocols designed for easy transfer into the lab and adaptation to new species.